Impact of computerization on the Philippine tourism industry - Covar, Ronora A.; Madamba, Noeme Gertrude Asteria F.; Padolina, Maria Riza B.; Santos, Maria Theresa U. (College of Engineering, 1986)
This study aims to determine how computerization has affected the Philippines tourism industry. It also attempts to determine how widespread is the use of computers in hotels, airlines, and travel agencies. This study is significant because it will help in increasing the people's awareness of the various uses of computers and in tapping the potentials of computers in the tourism industry. The study was conducted for about two months. Gathering of data was done primarily through taped interviews of hotel and airline managers and clerks, and travel agents. Considering that computerized systems have been in place from four to ten years before the study began, many areas have already been automated. In hotels, computers are used in the Front Office, Back Office, Accounting Department, and Business Centre. In airlines, computers are used in reservations, international cargo, ticketing, and information counters. In travel agencies, computers are used only in passenger reservations counter. Computerization has greatly improved the service rendered by the people of the tourism industry. It has not, however, contributed to the increase or decrease of the number of hotel rooms or airline seats sold. This study therefore concludes that computers, per se, play a minimal role in attracting tourists because there are other facotrs involved in promoting tourism. Maximizing the uses of current computer applications and improving the PLDT line are recommended for the development of the automated hotel and airline systems.